2020
DOI: 10.1017/prm.2020.20
|View full text |Cite
|
Sign up to set email alerts
|

All finite transitive graphs admit a self-adjoint free semigroupoid algebra

Abstract: In this paper we show that every non-cycle finite transitive directed graph has a Cuntz-Krieger family whose WOT-closed algebra is B(H). This is accomplished through a new construction that reduces this problem to in-degree 2-regular graphs, which is then treated by applying the periodic Road Coloring Theorem of Béal and Perrin. As a consequence we show that finite disjoint unions of finite transitive directed graphs are exactly those finite graphs which admit self-adjoint free semigroupoid algebras.2010 Mathe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…This question had recently been resolved positively. In fact, in[20] it is shown that every non-cycle finite transitive graph has B(H) as a free semigroupoid algebra.…”
mentioning
confidence: 99%
“…This question had recently been resolved positively. In fact, in[20] it is shown that every non-cycle finite transitive graph has B(H) as a free semigroupoid algebra.…”
mentioning
confidence: 99%